(untitled) (Global Journal of Medical Research, 2024)
In Eastern Asia, pulse diagnostics has been used before acupuncture treatments since time immemorial until today. All doctors practicing pulse diagnosis know that the pulse of males is stronger on the right hand and the pulse of females is stronger in the left hand, so they always check the pulse of males on the right hand and the pulse of females on the left hand [1]. Nobody ever explained why things are the way they were found to be, but I intend to explain this in this article. Also, all eye doctors should know that normally the right eye of males is stronger than the left eye and the difference is 0.25 diopter, while for females the left eye is stronger than the right eye and the difference is the same 0.25 diopter [2]. The eye doctors don’t study this at the medical schools, and even after many years of practice, they usually don’t have conscious awareness of this.